Ketidakberadaban mahasiswa dalam berbahasa: Studi kasus penggunaan media sosial dalam berinteraksi - Nisak, Khoirotun (Maliki Interdisciplinary Journal, 2023)
This research investigates students’ lack of civility in language, focusing on social media interactions and the reasons behind impolite language and slang, particularly among Muslim students. The qualitative and descriptive approach was used, with primary data obtained from student social media accounts. The analysis revealed that many students ignore good and polite grammar, even in social media interactions. The rampant use of slang, particularly in English, and harsh words in Indonesian communication on social media indicate a lack of understanding of proper grammar. The study concludes that character education and religious values should be emphasized in college curriculums to develop students with good morals and civilized communication skills. Family, community, and environment also play a role in shaping students’ character and behavior. Joint efforts are needed to overcome the challenges of uncivilization in language in the digital era and social media.